Complications of ultrasound-guided percutaneous native kidney biopsies in children: A single center experience - Asiri, Ali H; AlQarni, Musaed A; Bafaqeeh, Mohammed S; Altalhi, Abdulhadi M; Alshathri, Abdulaziz A; Alsaran, Khalid A (Journal of Clinical Nephrology, 2023)
Introduction: Percutaneous kidney biopsy is a necessary tool to diagnose many kidney diseases. However, major complications were reported in adults, including bleeding in the kidney or around it, creation of arteriovenous fistula, wound infection, damage to adjacent organs, or even loss of the kidney. Such complications can rapidly develop serious consequences. Exploring risk factors might help in preventing them. Objective: The current study aims to evaluate and explore the complications that happened after percutaneous kidney biopsy in children and associated risk factors. Methodology: A retrospective record-based study was conducted by reviewing the medical records of children with post-ultrasound-guided percutaneous kidney biopsy complications at King Saud Medical City, a tertiary hospital in Riyadh, Saudi Arabia during the period from May 2014 to June 2021. Data were extracted using pre-structured data collection sheet. Data collected included children’s age, gender, primary disease, laboratory findings, and kidney complications with needed management. Results: The study identified 76 children who had undergone 86 ultrasound-guided percutaneous kidney biopsies in the study period and fulfil the inclusion criteria. Children’s ages ranged from 1 years to 15 years with a mean age of 7.3 ± 4.0 years old. Most of the study children had nephrotic syndrome (61.6%; 53), followed by glomerulonephritis (25.6%; 22). Thirty-five (40.7%) children developed at least one of the complications. The most-reported complication was microscopic haematuria (32.6%; 28), followed by gross haematuria (3.5%; 3), Flank pain was reported among 3 (3.5%) children also and hematoma (1 child), only 2 children (3.9%) among those who had no complications recorded Haemoglobin drop > 2 g/dl compared to 3 of those who had complications with no statistical significance (p = .365). Prothrombin time was significantly higher among children who had renal complications than others who had not (11.7 ± 1.8 vs. 10.8 ± 1.2 seconds; p = .022). Conclusion: Suggestive by the low need to intervene in complications, ultrasound-guided percutaneous kidney biopsy is a relatively safe procedure in children. Even in the most commonly observed complication, i.e. hemorrhagic ones, blood transfusion is rarely needed.